2005
DOI: 10.1111/j.1600-0609.2005.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DXA, QCT and trabecular structure in β‐thalassaemia

Abstract: Osteopathy, as a major feature of homozygous beta-thalassaemia, is a multifactorial disorder, not fully understood. We studied the lumbar vertebrae of 48 patients using Dual-Energy X-ray Absorptiometry (DXA) and Quantitative Computed Tomography (QCT), and we focused on structural properties, assessed by High Resolution Computed Tomography (HRCT). Bone Mineral Density (BMD) values were expressed as Z-scores and the results were correlated. The effect of age, sex, and type of thalassaemia and hormonal factors on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
1
22
0
2
Order By: Relevance
“…In a study of 48 patients, the correlation coefficient between DXA BMD and QCT trabecular BMD was 0.545 (P Ͻ .001). The classification of patients into normal, osteopenia and osteoporotic categories, using QCT Z scores, was in better agreement with the assignment based on trabecular number (k ϭ 0.209, P ϭ .053) than the classification using DXA Z scores (k ϭ 0.145, P ϭ .12) (186). Another study employing peripheral QCT showed lower tibial trabecular volumetric BMD, cortical area, cortical bone mineral content, cortical thickness, periosteal circumference and section modulus Z-scores in thalassemic patients compared to controls (52).…”
Section: Peripheral Quantitative Computer Tomographymentioning
confidence: 91%
“…In a study of 48 patients, the correlation coefficient between DXA BMD and QCT trabecular BMD was 0.545 (P Ͻ .001). The classification of patients into normal, osteopenia and osteoporotic categories, using QCT Z scores, was in better agreement with the assignment based on trabecular number (k ϭ 0.209, P ϭ .053) than the classification using DXA Z scores (k ϭ 0.145, P ϭ .12) (186). Another study employing peripheral QCT showed lower tibial trabecular volumetric BMD, cortical area, cortical bone mineral content, cortical thickness, periosteal circumference and section modulus Z-scores in thalassemic patients compared to controls (52).…”
Section: Peripheral Quantitative Computer Tomographymentioning
confidence: 91%
“…In a previous study aimed at comparing DXA and quantitative computed tomography (QCT), Mylona and colleagues observed a strong difference in the prevalence of osteopenia and osteoporosis in patients with β-thalassemia according to the technique used. In this study we observed a different prevalence of osteoporosis for DXA and QUS 15. The classification of our patient into normal, osteopenic, and osteoporotic categories is exclusively based on T score values.…”
Section: Discussionmentioning
confidence: 65%
“…23,26,28 Present study showed that lower BMD values are associated with history of hypothyroidism, gonadal dysfunction or impaired puberty which reflects that low BMD values are found more commonly in the background of endocrinopathies. According to some authors [25][26][27]29 gonadal dysfunction probably has the most dominant role in the pathogenesis of bone disease in thalassemia major. So, for normal bone health can be attained by management of endocrine complications.…”
Section: Discussionmentioning
confidence: 99%
“…BMD Z-score significantly deteriorates with age, based on our study findings and those of others. 23,[25][26][27][28] There is possibility of having high prevalence of endocrine complications at an early age due to suboptimal transfusions and chelation therapy in patients with early age group. Quality of life is more strongly affected in older patients.…”
Section: Discussionmentioning
confidence: 99%